2016
DOI: 10.7554/elife.10807
|View full text |Cite
|
Sign up to set email alerts
|

Recombinational branch migration by the RadA/Sms paralog of RecA in Escherichia coli

Abstract: RadA (also known as 'Sms') is a highly conserved protein, found in almost all eubacteria and plants, with sequence similarity to the RecA strand exchange protein and a role in homologous recombination. We investigate here the biochemical properties of the E. coli RadA protein and several mutant forms. RadA is a DNA-dependent ATPase, a DNA-binding protein and can stimulate the branch migration phase of RecA-mediated strand transfer reactions. RadA cannot mediate synaptic pairing between homologous DNA molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 77 publications
2
78
0
Order By: Relevance
“…6A and Table 3). In E. coli, it has been shown that dsDNA and ssDNA stimulate the ATPase activity of RadA at the same level (23). Our data suggest that dsDNA and ssDNA have different actions on the ATPase activity of RadA.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…6A and Table 3). In E. coli, it has been shown that dsDNA and ssDNA stimulate the ATPase activity of RadA at the same level (23). Our data suggest that dsDNA and ssDNA have different actions on the ATPase activity of RadA.…”
mentioning
confidence: 51%
“…3, A and B). Interestingly, it has been shown that E. coli RadA requires ADP for DNA-binding activity, suggesting the ATPase domain has an important role for DNA binding (23). Further biochemical analysis and structural information about full-length RadA and its DNA complex are necessary for a complete understanding of how the rLonC and ATPase domains coordinate to regulate DNA-binding activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RADβ class is a divergent class of proteins that genetically function with RAD51 and are collectively known as the RAD51 paralogs. These paralogs are RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3 proteins in mammals, Rad55 and Rad57 as well as Csm2 and Psy3 in fungi, and RadB in archaea; recently, RadA of E. coli (not to be confused with RadA of Archaea), which is a member of this RADβ class, was shown to be a novel branch migration enzyme [7]. Many of the eukaryotic paralogs form various sub-complexes [8].…”
Section: Reca: a Molecular Search Enginementioning
confidence: 99%
“…The ATPase activity of RadD was necessary for this effect, with an ATPase-dead RadD displaying a dominant negative effect in response to UV. This role also showed overlap with the functions of RadA, a RecA paralogue involved in homologous recombination (22,23), and RecG, a superfamily 2 helicase involved in stabilizing recombination intermediates and preventing origin-independent replication (24,25).…”
Section: Discussionmentioning
confidence: 97%